Is explosive performance influenced by androgen concentrations in young male soccer players? - Baldari, C.; Di Luigi, L.; Emerenziani, G. P.; Gallotta, M. C.; Sgrò, P.; Guidetti, L. (British Journal of Sports Medicine, 2009)
Objective: There is growing interest in the implementation and assessment of strength and conditioning programmes among young children. The purpose of this study was to examine the association between given anthropometric characteristics, pubertal development, salivary androgen hormones and explosive leg power in young soccer players. Methods: 51 (age range 10-14 years) soccer players were investigated. The relations between age, pubertal developmental stages, testicular volume, weight, height, body fat, fat free mass, salivary DHEAS concentrations, salivary testosterone concentrations and lower limb explosive power were evaluated. Results: Standing long jump length was positively correlated (p,0.05) with age (11.7 (SD 1.2) years, r=0.66), pubertal developmental stages (mode and range: 1 (1-4), r=0.64), testicular volume (8.8 (5.2) ml, r=0.58), height (1.50 (0.10) m, r=0.34), weight (43.7 (9.1) kg, r=0.34), fat free mass (35.4 (7.2) kg, r=0.67), salivary DHEAS concentrations (4.4 (1.2) ng/ml, r=0.38) and negatively correlated with body fat (18.6 (7.0) kg; r=20.49, p,0.05). There was no significant correlation between salivary testosterone concentrations (0.3 (0.1) ng/ml, r=0.12) and standing long jump. Conclusions: Results of the present investigation demonstrated that age, pubertal developmental stages, testicular volume, weight, height, fat free mass, and salivary DHEAS concentrations were associated with standing long jump performance. In addition, salivary testosterone concentrations were not related to explosive leg power. Results of the present investigation suggest that the teacher/coach should evaluate long jump performance relative to the subject`s given biological characteristics, and not simply established standards based on chronological age.